Family cluster of Chagas disease among Bolivian immigrants in Italy: High rate of maternal-fetal transmission. Issue 49 (September 2022) - Antinori, Spinello; Galimberti, Laura; Grande, Romualdo; Ricaboni, Davide; Sala, Stefania; Giacomet, Vania; Colombo, Valeria; Corbellino, Mario; Angheben, Andrea; Giacomelli, Andrea; Ridolfo, Anna Lisa
Abstract: Background: Chagas disease (CD) or American trypanosomiasis is a neglected anthropozoonosis caused by Trypanosoma cruzi that affects 6–8 million people worldwide (mainly in Latin America), 30–40% of whom develop cardiac or digestive complications. Once confined to endemic areas of Latin America, CD has more recently become a global disease as a result of migration flows from endemic to non-endemic regions, particularly in northern America and Europe. Congenital transmission is a particular challenge as it may be sustained for multiple generations and perpetuate the infection even in non-endemic countries. Methods: Subjects were identified during a cross-sectional survey of CD among Latin American people living in Milan, Italy. Serology was carried out using tests based on either a lysate and a recombinant antigen of Trypanosoma cruzi . They were also tested by a conventional Polymerase Chain Reaction (PCR) targeting the 330 bp variable region of the T. cruzi kinetoplast minicircle genome and a commercial real-time PCR. Results: We here describe a Bolivian family cluster with seven affected people with at least two autochthonous congenital T. cruzi infection which was identified during the course of a CD screening programme. We also review the epidemiology, diagnosis and control of congenital CD, with particular emphasis on the challenges facing the control and management of such a complex and still largely hidden disease. Conclusions: Our experience confirms the need to screen for CD all family members once a case is diagnosed and shows the possible high rate of congenital CD also in non-endemic areas.